Și, totuși, virtuțile contează și astăzi (Verbum. Revista de teologie catolică, 2025)
This article explores the enduring relevance of the cardinal and theological virtues, focusing on their systematic treatment in Thomas Aquinas’s Summa Theologiae and their reinterpretation in modern virtue ethics. It examines the structure and interrelation of virtues and vices in Aquinas, highlighting the role of prudentia as a keystone of moral reasoning. Drawing on thinkers such as Elizabeth Anscombe, Alasdair MacIntyre, Charles Taylor, and Pierre Bourdieu, the study connects Aquinas’s philosophical theology with contemporary debates on character formation, social ethics, and the potential for moral transformation within communities. Thearticle argues for the civic and practical utility of virtues in both personal development and societal cohesion.